Simulation analysis and verification of brake shoe wear for urban rail vehicles - XUE Wensheng; ZHU Wenliang; YU Chaogang; SUN Ningyuan (机车电传动)
Frequent braking applications for speed regulation of urban rail vehicles cause repeated friction at elevated temperatures between the wheels and brake shoes, which accelerates brake shoe wear. This paper presents a study of wear patterns for brake shoes subjected to braking-induced temperature rise. For this purpose, a finite element model of the wheel and brake shoe friction pair and a simulation model to predicate brake shoe wear based on temperature changes were established. Additionally, the finite element software ABAQUS was used to implement the Archard model for calculating brake shoe wear in relation to temperature changes. Subsequent analysis investigated the wear patterns of brake shoes under three specific conditions: single emergency braking, single maximum electro-pneumatic service braking, and continuous braking. Finally, the rationality and correctness of the proposed simulation method were verified by comparing the results of brake shoe wear simulations with data from vehicle testing conducted on the real-world track. The results indicate that temperature changes cause variations in the properties of brake shoe materials. Under the single emergency braking condition, the prediction model considering temperature changes resulted in an increase in brake shoe wear of 43.8% compared to the prediction model without taking these changes into account. Under the single maximum electro-pneumatic service braking condition, the highest brake shoe wear was identified on trailers air braking force with priority supplement, which was recorded at 14.6×10-3 mm. Under the continuous braking condition, the predicted average wear rate of brake shoes was 0.28 mm/104 km, which closely aligned with the wear rate of 0.27 mm/104 km measured on the test vehicle. The established prediction model for brake shoes offers a reference for further studying the wear patterns of brake shoes for urban rail vehicles.